Differential effect of anthracycline and trastuzumab cancer therapeutic related vascular toxicity in patients with breast cancer. (25th November 2020) - Anastasiou, M; Oikonomou, E; Vogiatzi, G; Siasos, G; Flora, Z; Antonopoulos, A.S; Tsalamandris, S; Bamias, A; Dimopoulos, M.A; Tousoulis, D
Abstract: Introduction: Both anthracyclines and trastuzumab are key regiments for the treatment of breast cancer, but their concurrent use is contraindicated because of their cardiotoxicity. Their effects on vascular function have been less well studied. Purpose: We explored the effects of the anthracycline-based chemotherapy followed by trastuzumab-based treatment on endothelial function and arterial stiffness in patients with breast cancer. Methods: 46 female patients (54.56±11.5 years old) with breast cancer scheduled for anthracycline-based chemotherapy followed by the combination of trastuzumab and taxane were enrolled. Trastuzumab was continued until the completion of one-year treatment. All participants underwent assessment of the brachial flow mediated dilatation (FMD), endothelial independent dilatation (EID), carotid-femoral pulse wave velocity (PWV) and augmentation index (AIx) at baseline (BL), at the end of anthracycline treatment (FU1), 3 months following initiation of trastuzumab with taxane (FU2) and at the completion of treatment with trastuzumab (FU3). Results: Over the follow-up period (15 months) there was significant deterioration in FMD (p=0.04) (Table 1, Figure 1). Importantly, while there was no significant difference in FMD between BL vs FU1 (p=0.6), FMD has been significantly deteriorated over the treatment with trastuzumab with taxane FU1 vs FU2 (p=0.01) and FU2 vs FU3 (p=0.01) (Table 1, Figure 1). EID did not change over the follow-up period (Figure 1). Similarly, PWV has been significantly increased over the follow up period (p=0.03). There was no significant difference in PWV BL vs FU1 (p=0.1), however PWV has been significantly increased over the treatment with trastuzumab with taxane FU1 vs FU 2 (p=0.02) and FU2 vs FU3 (p=0.01) (Table 1, Figure 1). A similar pattern of impairment was observed with AIx (Table 1, Figure 1). Conclusion: We report a significant adverse effect of the anthracycline- and trastuzumab-based therapy on the arterial stiffness and endothelial function. This effect is more considerable after the exposure to trastuzumab. Funding Acknowledgement: Type of funding source: None